Effective Delivery of Hypertrophic miRNA Inhibitor by Cholesterol‐Containing Nanocarriers for Preventing Pressure Overload Induced Cardiac Hypertrophy. Issue 11 (6th April 2019) - Zhi, Ying; Xu, Chen; Sui, Dandan; Du, Jie; Xu, Fu‐Jian; Li, Yulin
Abstract: Persistent cardiac hypertrophy causes heart failure and sudden death. Gene therapy is a promising intervention for this disease, but is limited by the lack of effective delivery systems. Herein, it is reported that CHO‐PGEA (cholesterol (CHO)‐terminated ethanolamine‐aminated poly(glycidyl methacrylate)) can efficiently condense small RNAs into nanosystems for preventing cardiac hypertrophy. CHO‐PGEA contains two features: 1) lipophilic cholesterol groups enhance transfection efficiency in cardiomyocytes, 2) abundant hydrophilic hydroxyl groups benefit biocompatibility. miR‐182, which is known to downregulate forkhead box O3, is selected as an intervention target and can be blocked by synthetic small RNA inhibitor of miR‐182 (miR‐182‐in). CHO‐PGEA can efficiently deliver miR‐182‐in into hearts. In the mice with aortic coarctation, CHO‐PEGA/miR‐182‐in significantly suppresses cardiac hypertrophy without organ injury. This work demonstrates that CHO‐PGEA/miRNA nanosystems are very promising for RNA‐based therapeutics to treat heart diseases. Abstract : In this work, CHO‐PGEA (cholesterol‐terminated ethanolamine‐aminated poly(glycidyl methacrylate)) is proposed for gene therapy of cardiac hypertrophy. miR‐182 inhibitor (miR‐182‐in) is a synthetic small RNA inhibitor of miR‐182 which is known to downregulate forkhead box O3. CHO‐PGEA/miR‐182‐in complex can efficiently enter into cardiomyocytes and significantly suppress cardiac hypertrophy without organ injury.